Iowa RBA, November 22-25, 1999 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1999)
Four emails of Iowa RBA updates for November 22-25, 1999. Highlights of the updates include sightings of two Black-billed Magpies, Lesser Black-backed Gull, Red Crossbill, Eurasian Collared Doves, and a Pomarine Jaeger. Epson - sheet feed/flatbed